PENGARUH KOMITE AUDIT,TIME BUDGET PRESSURE,AUDIT TENURE,ROTASI AUDIT,DAN FEE AUDIT TERHADAP KUALITAS AUDIT (STUDI PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BEI TAHUN 2022-2024) - Hanaya Tarigan, Eunice; Rayani Simangunsong, Friska (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to examine the effect of audit committee, time budget pressure, audit tenure, audit rotation, and audit fee on audit quality (study on transportation companies listed on the IDX in 2022-2024) using quantitative methods with multiple linear regression. The data used in this study are secondary data in the form of financial statements of transportation sector companies 2022-2024 consisting of 12 samples. The results of this study indicate that audit committee, time budget pressure, audit tenure, audit rotation, and audit fee have a significant effect on audit quality. The coefficient of determination test shows that the Adjusted R Square value is 0.790 or 79%. This means that the dependent variable can be explained by the independent variables, namely Audit Committee, Time Budget Pressure, Audit Tenure, Audit Rotation, and Audit Fee by 79%, while the remaining 21% is explained by other variables outside this research model.